2013
DOI: 10.1002/stem.1461
|View full text |Cite
|
Sign up to set email alerts
|

Reversing bone loss by directing mesenchymal stem cells to bone

Abstract: Bone regeneration by systemic transplantation of mesenchymal stem cells (MSCs) is problematic due to the inability to control the MSCs’ commitment, growth and differentiation into functional osteoblasts on the bone surface. Our research group has developed a method to direct the MSCs to the bone surface by conjugating a synthetic peptidomimetic ligand (LLP2A) that has high affinity for activated α4β1 integrin on the MSC surface, with a bisphosphonates (alendronate) that has high affinity for bone (LLP2A-Ale), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
86
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 82 publications
(93 citation statements)
references
References 65 publications
(86 reference statements)
7
86
0
Order By: Relevance
“…In this context, a recent study from our group found the nonpsychoactive phytocannabinoid, cannabidiol, to enhance the migratory potential of human mesenchymal stem cells (MSCs) ( 33 ). It is noteworthy that the pluripotent MSCs contribute to healing processes of injured tissues such as myocardium ( 34,35 ), injured spots of the eye ( 36 ), and bone tissue ( 37,38 ). Thus endocannabinoids and endocannabinoid-like substances, as well as enzymes that degrade these substances, are discussed as an endogenous system that regulates the differentiation of neural tissue (39)(40)(41), modulates embryogenesis ( 42 ), and coordinates remodeling of bone tissue ( 43 ).…”
Section: Migration Assaymentioning
confidence: 99%
“…In this context, a recent study from our group found the nonpsychoactive phytocannabinoid, cannabidiol, to enhance the migratory potential of human mesenchymal stem cells (MSCs) ( 33 ). It is noteworthy that the pluripotent MSCs contribute to healing processes of injured tissues such as myocardium ( 34,35 ), injured spots of the eye ( 36 ), and bone tissue ( 37,38 ). Thus endocannabinoids and endocannabinoid-like substances, as well as enzymes that degrade these substances, are discussed as an endogenous system that regulates the differentiation of neural tissue (39)(40)(41), modulates embryogenesis ( 42 ), and coordinates remodeling of bone tissue ( 43 ).…”
Section: Migration Assaymentioning
confidence: 99%
“…Osteoblastogenesis precedes propagation of mineral onto an extracellular matrix (ECM) consisted of collagen fibrils, osteocalcin, and osteopontin (OPN) secreted by the differentiating MSCs 2. Nanocrystal nucleation of apatite subsequently forms on such mineralized ECM.…”
Section: Introductionmentioning
confidence: 99%
“…Manuscripts covered many advances in understanding the fundamental mechanisms that control stem and progenitor cell fate, and advances in working toward treating all tissues, from the lower extremities to the brain. Exciting basic and translational research was reported in using stem cells to treat osteoporosis [11], spinal cord injuries [12,13], radiation-induced fibrosis [14], glaucoma [15], globoid cell leukodystrophy [16], stroke [17], and Huntington's disease [18], to name just a few. It has truly been an exciting year, as we watch the stem cell field explode.…”
mentioning
confidence: 99%